Micro-computed tomography evaluation of root canal filling quality with apical negative pressure. (September 2020) - Li, Jinxia; Bergeron, Brian E.; Chao, Jing; Xu, Ting; Tay, Franklin R.; Fan, Bing
Abstract: Objectives: The objective of the present study was to compare, using micro-computed tomography (micro-CT), the location and volume percentage of voids in root canals that were obturated with a premixed tricalcium silicate sealer and a single gutta-percha master cone, in the presence or absence of apical negative pressure. Methods: Twenty extracted human mandibular premolars were cleaned and shaped. The teeth were assigned to 2 groups (n = 10) according to the filling technique: apical negative pressure sealer application combined with the single-cone technique (NPS) or syringe-assisted sealer application combined with the single-cone technique (SS). Each specimen was scanned using micro-CT at 10 μm resolution. The percentages of voids were calculated from segmental regions of interest. Data were analysed using nonparametric statistical methods, with statistical significance pre-set at α = 0.05. Results: Significant difference was identified (p < 0.05) in the overall percentage of voids between the NPS group (0.33 %; interquartile range 0.25 %) and the SS group (6.29 %; interquartile range 5.57 %). In the NPS group, the percentages of voids in the coronal-third or middle-third of the canal space were statistically lower than that in apical-third (p < 0.0167, Bonferroni adjustment), with no significant difference between the former two groups. In the SS group, no significant difference in the percentages of voids was identified among the coronal-third, middle-third and apical-third of the canal space. Conclusions: Apical negative pressure sealer application combined with the single-cone technique produces fewer voids in root canal fillings than the conventional single-cone technique. Clinical significance: The apical negative pressure sealer application technique combined with single-cone filling constitutes a novel root canal obturation technique that improves the quality of root canal filling by minimising the volume of voids within the three-dimensional canal space.